Translation and linguistic validation of the Composite Autonomic Symptom Score COMPASS 31 - Pierangeli, Giulia; Turrini, Alessandra; Giannini, Giulia; Del Sorbo, Francesca; Calandra-Buonaura, Giovanna; Guaraldi, Pietro; Bacchi Reggiani, Maria Letizia; Cortelli, Pietro (Neurological sciences, 2015)
The aim of our study was to translate and to do a linguistic validation of the Composite Autonomic Symptom Score COMPASS 31. COMPASS 31 is a self-assessment instrument including 31 items assessing six domains of autonomic functions: orthostatic intolerance, vasomotor, secretomotor, gastrointestinal, bladder, and pupillomotor functions. This questionnaire has been created by the Autonomic group of the Mayo Clinic from two previous versions: the Autonomic Symptom Profile (ASP) composed of 169 items and the following COMPASS with 72 items selected from the ASP. We translated the questionnaire by means of a standardized forward and back-translation procedure. Thirty-six subjects, 25 patients with autonomic failure of different aethiologies and 11 healthy controls filled in the COMPASS 31 twice, 4 ± 1 weeks apart, once in Italian and once in English in a randomized order. The test–retest showed a significant correlation between the Italian and the English versions as total score. The evaluation of single domains by means of Pearson correlation when applicable or by means of Spearman test showed a significant correlation between the English and the Italian COMPASS 31 version for all clinical domains except the vasomotor one for the lack of scoring. The comparison between the patients with autonomic failure and healthy control groups showed significantly higher total scores in patients with respect to controls confirming the high sensitivity of COMPASS 31 in revealing autonomic symptoms.